A branch-leaf-like hierarchical self-supporting electrode as a highly efficient catalyst for hydrogen evolution. (2nd June 2021) - Zhang, Yuekun; Yan, Gang; Shi, Yue; Tan, Huaqiao; Li, Yangguang
Abstract : A composite electrocatalyst with a branch-leaf-like structure (MoNi4 /MoO3− x /NiCo@NF) was prepared, and hydrogen evolution reaction activity was studied. Abstract : Inspired by the advanced branch-leaf hierarchical structure of natural trees, a composite catalyst with a branch-leaf-like hierarchical structure was reported for the first time. This catalyst, which grows on Ni foam, consists of NiCo alloy nanobranches and MoO3− x nanoleaves embedded with MoNi4 nanoparticles. The NiCo alloy nanobranches as an electron transfer highway can effectively improve the conductivity of the catalyst. The MoO3− x nanoleaves not only provide HER active sites, i.e. water dissociation center (MoO3− x ) and Hads adsorption/desorption center (MoNi4 ), but also increase the specific surface area, expose more active sites and promote the mass transfer of the catalyst. Benefiting from the branch-leaf hierarchical structure and synergistic effect of the components, this composite catalyst exhibits high HER activity which is comparable to that of 20% Pt/C in the alkaline solution. It requires a very low overpotential (33 mV) to reach 10 mA cm −2, and the Tafel slope is only 34 mV dec −1 . The HER activity of the catalyst in simulated seawater is better than that of 20% Pt/C. This work shows a meaningful reference for the design and synthesis of a high efficiency non-noble metal HER catalyst used in alkaline water electrolysis.